Covering and Re-Covering the Heart: Development and Regeneration of the Epicardium - Yingxi Cao; Jingli Cao (Journal of Cardiovascular Development and Disease, 2018)
The epicardium, a mesothelial layer that envelops vertebrate hearts, has become a therapeutic target in cardiac repair strategies because of its vital role in heart development and cardiac injury response. Epicardial cells serve as a progenitor cell source and signaling center during both heart development and regeneration. The importance of the epicardium in cardiac repair strategies has been reemphasized by recent progress regarding its requirement for heart regeneration in zebrafish, and by the ability of patches with epicardial factors to restore cardiac function following myocardial infarction in mammals. The live surveillance of epicardial development and regeneration using zebrafish has provided new insights into this topic. In this review, we provide updated knowledge about epicardial development and regeneration.